Balancing of energy flows in a life cycle of thermal energy production from biogas - Slobodan Cvetković; Mirjana Kijevčanin (Zaštita Materijala)
Biogas is a promising source for energy production in future energy systems. In this paper, the energy flows in the life cycle of a real biogas plant (Mirotin-Vrbas) for thermal energy production were considered, starting from corn silage production, cow manure transport, process of anaerobic digestion and biogas production, to the use of solid and liquid digestate for production of crops. Four energy indicators were used to evaluate energy flows in this work. The obtained results showed that this biogas system has a positive energy balance of 62.418 GJ and an energy efficiency of 6,1, which indicates that in terms of substitution of fossil fuel consumption, this system for heat production is a good alternative.